Religion, Identity and Power : Turkey and the Balkans in the Twenty-First Century - Öztürk, Ahmet Erdi; Haynes, Jeffrey ([United Kingdom] : Edinburgh University Press, 2021)
This book examines Turkey's ethno-religious activism and power-related political strategies in the Balkans between 2002 and 2020, the period under the rule of the Justice and Development Party (AKP), to determine the scopes of its activities in the region.
Foreword from Professor Jeffrey Haynes; List of Illustrations; List of Tables; Acknowledgements; Introduction; Part 1: Theory and History; 1. Multi-sided Roles of Religion, Identity and Power in Politics; 2. Turkey in the Balkans: From Late Ottoman to the 1970s; 3. Turkey as a Nascent Power in the Balkans: From the Özal Years to the AKP; Part 2: Turkey's Intense Transformation under AKP Rule; 4. Defensive and Active Years of the AKP; 5. Reactive and Aggressive Years of the AKP; Part 3: The AKP's New Turkey and its Reflections in the Balkans; 6. Service to the Global Ummah; 7. Exportation of Domestic Conflicts; 8. Interfering in the Internal Affairs of Host Countries; 9. Destabilising the Secular Environments of Host Countries; Conclusion: The New Turkey in the Balkans: An Ambiguous Actor?.
Includes bibliographical references (pages 221-234) and index.
eBooks on EBSCOhost
Keywords: AK Parti (Turkey); AK Parti (Turkey); Religion and politics -- Turkey; Religion and politics -- Balkan Peninsula; Turkey -- Foreign relations; Balkan Peninsula -- Foreign relations; Religion et politique -- Balkans; Balkans -- Relations extérieures.; POLITICAL SCIENCE / Comparative Politics; Diplomatic relations; Religion and politics; Balkan Peninsula; Turkey